The Reconstruction of Miao Identity and the Legitimization of Christianity: Perspectives from Yunnan Fieldwork and Epistemology - KONG, Deji (Journal of Research for Christianity in China (JRCC), 2025)
this research paper discusses the affair of the Miao nationality( distributed over Guizhou, Hunan, Yunnan, the Guangxi Zhuang Autonomous Region, Sichuan and Guang- dong ) build church in Kunming city. Based on the data, the author analysis the symbolic meaning and theoretical difficulties of the “building church” affair. In addition, according to discussing of travel industry and art perform, the article shows the ways of achieving Christian- ity legalization in current political background. Combining to historical document and knowl- edge analysis, we can find out the formation and transition of the Miao culture, then explain the feasibility of  “building church”.